Effect of allowable flow-rate variation and local head loss on maximum length of non-pressure compensated drip tape - de Andrade, Luiz Antonio; Saad, João Carlos Cury [UNESP]; Cosmo, Bruno Marcos Nunes [UNESP]; Costa, João Victor [UNESP]; Zanetti, Willian Aparecido Leoti [UNESP] (Instituto de Pesquisas Ambientais em Bacias Hidrograficas (IPABHi), 2021)
A challenge for the design of drip irrigation systems with non-pressure compensated emitters is to increase the maximum length of the lateral lines without significantly reducing water application uniformity. This work evaluated the effect of the flow-rate variation and the local head loss in the maximum length of drip tape with a non-pressure compensated flat emitter. The tests were carried out in a laboratory, using a collapsible drip tape non-pressure compensated in three 50-meter segments. The production line was configured to generate drip tapes without insertion of emitters and with closed emitters (0.30 m spacing). The experimental local head loss was compared with the Darcy-Weisbach equation's estimates using the Blasius friction factor. In the sequence, simulations were generated for the flow-rate variations of 10 and 20% for the emitter spacings of 0.30, 0.40, and 0.50m. The results showed that the local head loss had little influence on the lateral line's maximum length, generating variations of 2.5% on average. However, increasing the allowable flow rate variation from 10 to 20% resulted in a 34% increase in the lateral line maximum length. Also, the reduction in uniformity coefficients was less than 5%, enabling the indexes to remain above 90%. The adoption of higher flow rate variation values allowed gains in the lateral line length with a small decrease in uniformity, making it an alternative to reduce design and operational costs.
Efeito da variação de vazão permitida e da perda de carga localizada no comprimento máxima de fita gotejadora não compensada
Keywords: Emitter head loss; Lateral line length; Uniformity